Geometry Analysis and Effect of Turbulence Model on the Radial Rotor Turbo-Expander Design for Small Organic Rankine Cycle System - Arifin, Maulana; Pasek, Ari Darmawan; Eddy, Zaidan (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2015)
Organic Rankine Cycle (ORC) is one of the most promising technology for small electric power generations. The geometry analysis and the effect of turbulence model on the radial turbo-expanders design for small ORC power generation systems were discussed in this paper. The rotor blades and performance were calculated using several working fluids such as R134a, R143a, R245fa, n-Pentane, and R123. Subsequently, a numerical study was carried out in the fluid flow area with R134a and R123 as the working fluids. Analyses were performed using Computational Fluid Dynamics (CFD) ANSYS Multiphysics on two real gas models, with the k-epsilon and SST (shear stress transport) turbulence models. The result shows the distribution of Mach number, pressure, velocity and temperature along the rotor blade of the radial turbo-expanders and estimation of performance at various operating conditions. The operating conditions are as follow: 250,000 grid mesh flow area, real gas model SST at steady state condition, 0.4 kg/s of mass flow rate, 15,000 rpm rotor speed, 5 bar inlet pressure, and 373K inlet temperature. By using those conditions, CFD analysis shows that the turbo-expander able to produce 6.7 kW and 5.5 kW of power when using R134a and R123, respectively.